2010
DOI: 10.2116/analsci.26.1059
|View full text |Cite
|
Sign up to set email alerts
|

Voltammetric Detection of Biological Molecules Using Chopped Carbon Fiber

Abstract: Voltammetric detection of biological molecules was carried out using chopped carbon fibers produced from carbon fiber reinforced plastics that are biocompatible and inexpensive. Because chopped carbon fibers normally are covered with a sizing agent, they are difficult to use as an electrode. However, when the surface of a chopped carbon fiber was treated with ethanol and hydrochloric acid, it became conductive. To evaluate the functioning of chopped carbon fibers, voltammetric measurements of [Fe(CN)6] 3-were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Since CFs have a local structure similar to graphite, they are good electrical conductors with resistivity in the range from 9.5•10 −6 to 18•10 −6 Ωm. They can be utilized in voltammetric recognition of biological molecules [366], to make electrodes for neural recording [367,368], or the stimulation of cardiomyocytes [369]. Concerning regeneration medicine, CFs are mainly utilized to fabricate scaffolds for tissue repair.…”
Section: Carbon Fibersmentioning
confidence: 99%
“…Since CFs have a local structure similar to graphite, they are good electrical conductors with resistivity in the range from 9.5•10 −6 to 18•10 −6 Ωm. They can be utilized in voltammetric recognition of biological molecules [366], to make electrodes for neural recording [367,368], or the stimulation of cardiomyocytes [369]. Concerning regeneration medicine, CFs are mainly utilized to fabricate scaffolds for tissue repair.…”
Section: Carbon Fibersmentioning
confidence: 99%
“…However, from an electroanalysis point of view, the performance of electrodes made of carbon fibre microcylinder bundles (CFMBs) has been comparatively lower than that of other solid carbon electrodes, such as glassy carbon electrodes (GCEs) or screen-printed carbon electrodes (SPCEs). Although the CFMB material is available at low cost, as roving from several suppliers and application of it for biosensing would have a huge impact on research, studies of its use as an electrode material have been limited to a few analytes (e.g., FAD, NADH, ascorbic acid, p-aminophenol, glutathione) [14][15][16] or neural recordings [17].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, CFMB electrodes are typically protected with a polymer coating layer (epoxy, polyester, urethane) for fibre shielding and alignment [18], and it has been suggested that this coating may interfere with the electrochemical signal [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Carbon fibers have been studied biologically and used clinically in a wide variety of applications. By electrical conductivity, carbon fibers have been used for voltammetric recognition of biological molecules [ 24 ]. Also, a carbon fiber electrode has been used for neural recording [ 10 ].…”
Section: Introductionmentioning
confidence: 99%